OPTIMIZATION OF SURGICAL TREATMENT OF CHRONIC POSTTRAUMATIC ANTEROMEDIAL INSTABILITY OF SHOULDER JOINT AT THE BONE DEFECT OF ARTICULAR PROCESS OF THE SCAPULA - V. V. Monastyrev; V. A. Sorokovikov; V. Yu. Vasilyev (Acta Biomedica Scientifica, 2012)
Main reason of shoulder joint instability is bone defect of scapula cavity. The number of unsatisfactory outcomes after surgical treatment is still high. The aim. of the research was to improve surgical technique of treatment of patients with chronic posttraumatic anteromedial instability of shoulder joint at the bone defect of articular process of the scapula. Open controlled prospective randomized research was carried out in the clinics of SCRRS SB RAMS. Clinical effectiveness of proposed medical technology was proved on the basis of analysis of operative treatment of 34 patients during 6 months after the operation. We used Bristow - Latarjet bone plastics for comparison.